I lie? We lie! Why? Experimental evidence on a dishonesty shift in groups - Martin Kocher; Simeon Schudy; Lisa Spantig (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
Unethical behavior such as dishonesty, cheating and corruption occurs frequently in organizations or groups. Recent experimental evidence suggests that there is a stronger inclination to behave immorally in groups than individually. We ask if this is the case, and if so, why. Using a parsimonious laboratory setup, we study how individual behavior changes when deciding as a group member. We observe a strong dishonesty shift. This shift is mainly driven by communication within groups and turns out to be independent of whether group members face payoff commonality or not (i.e. whether other group members benefit from one's lie). Group members come up with and exchange more arguments for being dishonest than for complying with the norm of honesty. Thereby, group membership shifts the perception of the validity of the honesty norm and of its distribution in the population.
urn:nbn:de:bvb:19-epub-28966-1
Keywords: C91; C92; D03; 330; dishonesty; lying; group decisions; communication; norms; experiment